Violência conjugal e análise do discurso : instituições, sujeitos e sentidos - Nunes-Scardueli, Márcia Cristiane (Language and Law / Linguagem e Direito, 2017)
By building upon the theoretical assumptions of French Discourse Analysis, the doctoral research reported here analysed the meanings produced when the Brazilian Law No. 11.340/2006, which became widely known as the Maria da Penha Law, was applied by the Civil Police (investigation reports) and the Judiciary (court decisions). The discursive analysis of documents produced in twenty criminal cases from the District of Araranguá in the state of Santa Catarina, Brazil, during the period 2006 to 2013, in situations of marital domestic violence supplemented by analyses of interviews with female victims and male perpetrators, cited in the same processes, demonstrated that the system generalized the cases, due to pre-established legal discourse modeling, which standardizes the texts and silences the individual plots and life stories. The analyses also revealed that not only the acts of violence, but also the victims themselves were standardly silenced; a silencing that occurred not only through the judicial decisions that were reached, but also during interaction in the trials, which often ended up denying that violence occurred, thereby silencing the very question to be judged. The silencing of violence was also identied in the contributions of the women and men who were interviewed, as well in the gender stereotypes that reinforced the social positions occupied by the victims and the perpetrators. The results suggest that in reality the application of the Maria da Penha Law in cases of marital domestic violence is a mere formality, serving to maintain inequality in marital relations and strengthening the male x female duality.